Construção civil: crescimento versus curtos de produtividade - Vieira, Bianca Alencar (Universidade Federal Rural do Semi-Árido, 2017)
The country's economic growth is linked to the growth of several sectors, especially the industrial sector. Among them, stands out the Civil Construction. In this conjecture, the main objective of this study was to investigate the relationship between growth of the Civil Construction Industry in Brazil and its productivity costs in the period from 2000 to 2016. Two quantitative methodologies were adopted. The database was composed of information collected at the Institute of Applied Economic Research – IPEA and at the Brazilian Chamber of Construction Industry – CBIC. The main results indicate that: i) no valid statistical evidence has been found that proves any direct or indirect relation of the costs with the growth rates of the sector; ii) In turn, it was found that the main determinant of the construction industry is investment.
Keywords: PIB da construção civil; custos da construção; investimentos no setor; civil construction GDP; construction costs; investments in the sector; ENGENHARIAS::ENGENHARIA CIVIL